Quando a matéria importa (e como importa) - Ministro, Bruno (MATLIT: Materialities of Literature, 2021)
Recensão crítica de Rebecca Kosick, Material Poetics in Hemispheric America: Words and Objects 1950-2010. Edinburgh University Press, 2020. 240 pages. ISBN: 9781474474603 (Hardback), 9781474474627 (Ebook – PDF).